THERMAL BEHAVIOR IMPROVEMENT OF BIODEGRADABLE FIBER POLYMER COMPOSITES POLYLACTIC ACID (PLA)/COIR USING ACEH’S BENTONITE - Ridwan; Rihayat, Teuku; Ismy, Adi Saputra; Aidy, Nurhanifa; Ilmi, Awanis (International Journal of Research -GRANTHAALAYAH, 2021)
Research has been conducted on the manufacture of PLA Coir Bentonite composites. This study aims to examine the effect of PLA on mechanical strength with the addition of coir and bentonite fillers from North Aceh and Central Aceh. The sample formulations used were single polymer PLA/Coir and PLA/Coir with variations of filler Bentonite Aceh Utara and Aceh Tengah with 2, 4, 6 and 8% respectively. The combination of PCa samples showed the highest bacterial colony growth rate, which was more than 100 colonies/gram during the 1 week testing period. In the PBATd filler mixture sample, the maximum bacterial test value was 65 colonies/gram and the minimum value contained in the PBAUa sample was 105 colonies/gram. The best tensile strength was obtained in the PBATc sample, namely 65 MPa. PBATd samples began to degrade at 370.15oC compared to PCa samples degraded at 280.21oC. While the PBAUa sample began to degrade at a temperature of 282.11oC. The surface structure of the PCa sample is more homogeneous because there is no bentonite filler mixture, but it is brittle and crumbles easily. For the PBATd sample, the surface structure is smoother and more homogeneous compared to the PBAUa sample.